Palynology and palaeocommunities of the Paleogene of Argentina - Quattrocchio, Mirta Elena
Two major paleophytogeoprovinces based on the palynological record at the genus or species level and at the palaeocommunity level are recognized for the Danian of Argentina. The presence of Verrustephanoporites simplex (Ulmaceae) pollen in the north is associated mostly with tropical and subtropical families, while Nothofagidites pollen in the south is mostly associated with temperate families. In the centralnorthwest of Argentina, a subprovince with elater bearing pollen (Mtchedlishvilia) is recognized. Warm and humid climatic conditions are indicated for the Ulmaceae Phytogeoprovince and more temperate conditions for the Phytogeoprovince of Nothofagidites. Tropical to subtropical communities are recognized at the Early Eocene, being later replaced by “mixed forest” with both Neotropical and Antarctic elements, which occupied most of the emerged lands. Great paleogeographic and tectonic events affected Patagonia during the Oligocene and even more clearly at the Early Miocene, when an expansion of open vegetation patches with Chenopodiaceae, Ephedraceae, Asteraceae and Poaceae is recorded. These changes are interpreted as a consequence of strong arid trends related to the final uplift of the Andes, the formation of the West Antarctic ice cap, intensification of the cold Humboldt Current and the South Pacific Subtropical Anticyclone, as well as the beginning of the continental glaciation in Patagonia. Com base no registro palinológico em nível de gênero ou espécie e das paleocomunidades, se reconhecem duas paleofitogeoprovíncias no Daniano da Argentina. A presença de Verrustephanoporites simplex (Ulmaceae) no norte está associada, principalmente, com famílias tropicais e subtropicais, enquanto que Nothofagidites, no sul, está associado, principalmente, com comunidades vegetais temperadas. No centro e noroeste da Argentina, se distingue uma subprovíncia com grãos de pólen elaterados (Mtchedlishvilia). Condições climáticas quentes e úmidas são interpretadas para a Fitogeoprovíncia de Ulmaceae e mais temperadas ...